Analysis of Chosen Phonetic and Morphological Features Present in Polish Folk Songs in the Vilnius Region - Korycka, Anna (Respectus Philologicus, 2012)
This article is devoted to an analysis of certain phonetic and morphological features that occur in the material of Polish folk music in the Vilnius region. Excerpts were chosen with respect to the dominant linguistic elements (both phonetic and morphological) of the region in question. Examples were taken from Songs of Vilnius Region (Pieśni Wileńszczyzny) by Jan Mincewicz, materials gained from the Archive of the Institute of Lithuanian Literature and Folklore in Vilnius, and the author’s own recordings. Based on dialectological publications (Kurzowa, Grek-Pabisowa, Sawaniewska-Mochowa, Rieger and others), an investigation into the occurrence of specific features of Northern Borderlands Polish in the Polish folk songs of the Vilnius region was undertaken. The Polish community is a dynamic group, the vast majority nurturing their own culture, language and customs.The first section of the article analyzes the phonetic features connected with the system of vowels and consonants. The second section contains an analysis of morphological phenomena (inflectional and word formative) present in the Polish folk songs known and sung in the Vilnius region. It was found that certain nouns change their grammatical gender; such singularities occur in the presence of the verb and the suffix -uk. The structure of the dialect in the researched area has been preserved quite well, which can be confirmed by the frequency with which the features typical of this region occur.In conclusion, on the basis of phonetics and morphology, it can be stated that the language of the Polish folk songs known and sung in Vilnius has retained many features of the dialect specific to the Northern Polish Borderlands.
Keywords: folk song; phonetics; inflection; word formation; borderlands dialect; Vilnius region